SOME ISSUES OF SCIENTIFIC AND METHODICAL PROVISION OF UPBRINGING OF ADOLESCENTS IN THE SPIRIT OF MILITARY PATRIOTISM (World Bulletin of Management and Law, 2023)
The article talks about the possibilities of increasing the sense of patriotism of the citizens of the Republic of Uzbekistan, filling the ranks of our national army with young people who have modern knowledge and professional skills, strong will, active citizenship position, and education in the military-patriotic spirit will be carried out in four stages.